Clinicopathologic and endoscopic features of sessile serrated lesions and conventional adenomas: a large inpatient population-based study in China - Tan, Chang; Qin, Geng; Wang, Qian-Qian; Zhou, Yuan-Chen; Yao, Shu-Kun (Frontiers in Oncology, 2024)
Objectives Sessile serrated lesions (SSLs) are precursors of sporadic colorectal cancer (CRC) and have distinct characteristics compared with conventional adenomas (CAs). Several lifestyle and environmental factors may play critical roles in the development of advanced lesions. Our aim is to describe the features of SSLs and CAs and further explore risk factors for advanced lesions. Methods This is an observational study that collected demographic, endoscopic, and histological data from the China-Japan Friendship Hospital among the inpatient population with pathologically reported as SSL or CA between 2015 and 2022. We analyzed the clinicopathology and endoscopic differences between SSL alone, CA alone, and synchronous SSL+CA groups, and identified risk factors using multiple regression analysis. Results A total of 9236 polyps from 6598 patients were included in the cohort. Patients with SSL+CA were more likely to be older (p=0.008), while individuals with SSL alone had a higher proportion of early-onset polyps (p<0.001), and SSLs were more common in advanced polyps than CAs (p<0.001). A greater proportion of advanced polyps in the SSL and CA groups were diagnosed as Yamada III, Yamada IV, and laterally spreading tumor (p=0.002, p<0.001, respectively), and multiple SSLs and CAs were more represented in nonadvanced polyps than in advanced polyps. In multiple regression analysis, older patients were more likely to develop advanced SSLs (aOR 1.05, 95% CI 1.02-1.09, p=0.005). Conclusion SSLs and CAs have diverse demographic, endoscopic, and histological characteristics, and their advanced lesions share different risk factors, which advances the understanding of the etiology and progression of SSLs.